Genetic divergence among palm bacabi accessions by bunch and fruit characteristics (Research, Society and Development, 2026)
The palm bacabi (Oenocarpus mapora H. Karst.), an Amazonian palm with socioeconomic potential, is predominantly exploited through extractivism. The objective of this work was to quantify the genetic divergence among bacaba accessions conserved in the Active Germplasm Bank of Oenocarpus spp. (BAG Bacabas) of Embrapa Amazônia Oriental, based on characters related to bunches and fruits. Fourteen morpho-agronomic characters of bunches and fruits were evaluated using multivariate statistical analyses such as Euclidean distances, Tocher, UPGMA, relative character contribution, and Principal Component Analysis (PCA). Remarkable genetic variability was detected. Bunch characters, such as total bunch weight (PTC) and fruit weight per bunch (PFC), showed predominantly positive correlations of high magnitude. In the fruits, the weight of edible portion (PPC) revealed a strong positive correlation with the weight of one hundred fruits (PCF), the longitudinal diameter of the fruit (DLF), and the fruit weight (PF), highlighting the relevance of these characteristics for pulp yield. The identification of promising genotypes, such as 32 (high Yield of Edible Portion - RPC) and 2 (largest Transversal Diameter of the Fruit - DTF), and the understanding of correlations are crucial for selection and optimization of breeding. It is concluded that the study of genetic divergence is vital for the development of more productive palm bacabi cultivars with high pulp yield, facilitating the transition from the extractivist model to efficient cultivation systems and strengthening the production chain of this Amazonian species.